Susceptibility of Guinea Fowl (Numida Meleagris Galeata) to Infectious Bursal Disease Virus (IBDV) - Onyeanusi, B.I.; Onyeanusi, C.G.; Ibe, C.S. (International Journal of Poultry Science, 2009)
The experiment was carried out to determine whether the guinea fowls are susceptible to Infectious Bursal Disease Virus (IBDV). A total of 60 guinea fowl keets were used for the study. They were administered the inoculum through the intraocular route. 30 guinea fowl keets served as the control group (A) while, the other 30 served as the experimentally infected group (B). The only clinical signs observed in about 10 keets were mild depression and transient loss of appetite that did not last more that 24 h. The morphometric observations also indicated that the relative weights in the two groups (A and B) showed no Significant difference (p>0.05) in both the Control (group A) and Infected (group B) keets. It was concluded that guinea fowls are not susceptible to IBDV but they could severe as carriers, which would spread the virus to other poultry species if reared together with them.